Hotel service recovery and service quality: Influences of corporate image and generational diﬀerences in the relationship between customer satisfaction and loyalty - Cheng, Boon Liat *; Mansori, Shaheen; Gan, Chin Chuan *; Imrie, Brian C. * (Taylor & Francis, 2017)
As the number of tourists continues to grow globally, the hospitality industry players inevitably face more challenges. High competition among the competitors and the emergence of new technologies such as online booking platforms make the competition more intense among players in the hospitality sector. The quality of services provided is undoubtedly crucial to the success of the hotel. Hence, any service failure has to be addressed appropriately in order to maintain a high level of customer satisfaction and to keep the image of the hotel intact. It is therefore vital that service recovery programs are carefully planned to meet various types of service failures which may inevitably occur. In this study, questionnaires were distributed to customers who had experienced service failures. The aim was to investigate the influence of service quality and service recovery on satisfaction and, ultimately, the effect on customer loyalty. The research also tested the mediating effect of corporate image between the relationship of customer satisfaction and customer loyalty. The findings showed that both service recovery and service quality had a significant impact on customer satisfaction. Similarly, it was found that customer satisfaction induced customer loyalty towards the hotel operator. The result also showed that corporate image mediated partially between the relationship of customer satisfaction and customer loyalty.